(untitled) (Universa Medicina, 2011)
Bone remodeling is a physiological process of cortical and trabecular bone reconstruction, with initial bone resorption, by osteoclasts and concurrent bone formation by osteoblasts. Oxidative stress due to coal dust exposure is not only found in the lungs, but also in the circulation or systemically. The aim of this study was to determine the effect of oxidative stress from coal dust exposure on the number of osteoblasts and osteoclasts in rats. In this experimental study, four groups were evaluated: control; coal dust exposure at 6.25 mg/m3 for 28 days; coal dust exposure at 12.5 mg/m3 for 28 days; coal dust exposure at 25 mg/m3 for 28 days (all exposures were given daily for one hour). Circulatory oxidative stress was measured by malondialdehyde level. Osteoblast and osteoclast numbers were counted by light microscopic examination of distal femoral cross-sections stained with hematoxylin eosin. This study showed that malondialdehyde levels were significantly increased in coal dust exposure groups, in comparison with the control group (p<0.05). There were also significantly decreased numbers of osteoblasts (p<0.05) and significantly increased numbers of osteoclasts (p<0.05) numbers in coal dust exposure groups, as compared with the control group. No correlations were found between malondialdehyde levels (oxidative stress) and respective numbers of osteoblasts and osteoclasts in all coal dust exposure groups (p>0.05). Coal dust exposure increased malondialdehyde level and osteoclast numbers, and decreased osteoblast numbers, but no correlation was found between oxidative stress (caused by coal dust exposure) and osteoblast and osteoclast numbers.